Respostas
respondido por:
2
Resposta:
OLÁ
a) f(x) = -3x -12
0= -3x-12
3x=-12
x= -12/3
x= -4
b) f(x) = 2x -8
0=2x-8
-2x= -8
x= -8/-2
x= 4
Explicação passo-a-passo:
espero ter ajudado
miriamzimer28:
obrigada
respondido por:
1
Resposta
f(x) = -3x-12
1 passo : substituir
f(x) =0
0= - 3x- 12
3x= - 12
X= - 4
f(x) = 2x - 8
substituir
f(x) = 0
0 = 2x = - 8
- 2x = - 8
x = 4
f(x) = -3x-12
1 passo : substituir
f(x) =0
0= - 3x- 12
3x= - 12
X= - 4
f(x) = 2x - 8
substituir
f(x) = 0
0 = 2x = - 8
- 2x = - 8
x = 4
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás